The 30-kilodalton protein present in purified fusicoccin receptor preparations is a 14-3-3-like protein. - Marra, M (1994)
We have recently reported on the purification of the fusicoccin (FC) receptor from corn (Zea mays L.) and its identification by photoaffinity labeling (P. Aducci, A. Ballio, V. Fogliano, M.R. Fullone, M. Marra, N. Proietti [1993] Eur J Biochem 214: 339-345). Pure preparations of FC receptors, obtained under nondenaturing conditions, showed in sodium dodecyl sulfate-polyacrylamide gel electrophoresis two doublets of proteins with apparent molecular masses of 30 and 90 kD. In the present paper we describe the isolation and identification of the primary structure of the 30-kD doublet proteins. Sequencing studies of peptides resulting from the digestion of the 30-kD protein showed a full identity with a 14-3-3-like protein from corn, named GF14. The 14-3-3 family is a class of proteins that is widely distributed in eukaryotes and is known to play various regulatory roles. The 30-kD protein has been immunologically identified by specific antibodies prepared against a synthetic peptide based on the determined amino acid sequence. A similar protein is recognized in partially purified FC receptor preparations from bean and spinach leaves.